An integrated organic farming system: innovations for farm diversification, sustainability, and livelihood improvement of hill farmers - Layek, Jayanta; Das, Anup; Ansari, Meraj A.; Mishra, Vinay K.; Rangappa, Krishnappa; Ravisankar, Natesan; Patra, Sandip; Baiswar, Pankaj; Ramesh, Thangam; Hazarika, Samarendra; Panwar, Azad S.; Devi, Shidayaichenbi; et al. (Frontiers in Sustainable Food Systems, 2023)
Introduction Organic farming is a promising solution for mitigating environmental burdens related to input-intensive agricultural practices. The major challenge in organic agriculture is the non-availability of large quantities of organic inputs required for crop nutrition and sustaining soil health, which can be resolved by efficient recycling of the available on- and off-farm resources and the integration of the components as per the specific locations. Methods An integrated organic farming system (IOFS) model comprising agricultural and horticultural crops, rainwater harvesting units, livestock components, and provisions for nutrient recycling was developed and disseminated in the adopted organic villages Mynsain, Pynthor, and Umden Umbathiang in the Ri-Bhoi District, Meghalaya, India, to improve the income and livelihood of farmers. Harvested rainwater in farm ponds and Jalkunds was used for live-saving irrigation in the winter months and diversified homestead farming activities, such as growing high-value crops and rearing cattle, pigs, and poultry. Results Maize, french bean, potato, ginger, tomato, carrot, and chili yields in the IOFS model increased by 20%−30%, 40%−45%, 25%−30%, 33%−40%, 45%−50%, 37%−50%, and 27%−30%, respectively, compared with traditional practices. Some farmers produced vermicompost in vermibeds (made of high-density polyethylene) and cement brick chambers, generating 0.4−1.25 tons per annum. Two individual farmers, Mr. Jrill Makroh and Mrs. Skola Kurbah obtained net returns (without premium price) of Rs. 46,695 ± 418 and Rs. 31,102 ± 501 from their respective 0.27- and 0.21-ha IOFS models, which is equivalent to Rs. 172,944 ± 1,548/ha/year and Rs. 148,105 ± 2,385/ha/year, respectively. The net returns obtained from the IOFS models were significantly higher than those obtained from the farmers' practice of maize-fallow or cultivation of maize followed by vegetable (~30% of the areas). It is expected that, with the certification of organic products, the income and livelihood of the farmers will improve further over the years. While Mr. Jrill Makroh's model supplied 95.1%, 82.0%, and 96.0% of the total N, P2O5, and K2O, respectively, needed by the system, Mrs. Skola Kurbah's model supplied 76.0%, 68.6%, and 85.5% of the total N, P2O5, and K2O, respectively. Discussion Thus, IOFS models should be promoted among hill farmers so that they can efficiently recycle farm resources and increase their productivity, net returns, and livelihood while reducing their dependence on external farm inputs.